Crop simulation modelling: a hope in the climate change era - Nath, Anil; Pandey, Deepak (Indian Farming, 2018)
There is a growing concern that climate changes will lead to significant impact on agriculture, thus having a global effect in food production. Crop simulation models can be used to understand the effectsÂ of climate change such as consequences of elevated carbondioxide, Changes in temperature and rainfall on crop development, growth and yield etc. Crop growth model is a promising tool for predicting possible impacts of climatic variations on crop growth and yield. Different kinds of models such as statistical, stochastic, dynamic, static and simulations etc. are available for assessing the environment modification effects on crop growth and yield. These models are useful for solving various practical problems in agriculture, thus enabling more efficient and targeted research planning. Adequate human resource capacity has to be improved and validated simulation models have to be developed across the globe.